Hepatocellular carcinoma after direct‐acting antiviral drug treatment in patients with hepatitis C virus. Issue 1 (9th November 2018) - Kogiso, Tomomi; Sagawa, Takaomi; Kodama, Kazuhisa; Taniai, Makiko; Katagiri, Satoshi; Egawa, Hiroto; Yamamoto, Masakazu; Tokushige, Katsutoshi
Abstract : Background and Aim: Given the use of direct‐acting antivirals (DAAs) to treat hepatitis C virus (HCV), their effects on hepatocarcinogenesis should be determined. Methods: This study enrolled 349 patients with HCV who underwent DAA treatment at our hospital between 2014 and 2018. Their median age was 65 years, and 184 were male; 301 cases were of HCV serotype 1, and 48 were of serotype 2. The DAA treatment was daclatasvir/asunaprevir in 107 cases, sofosbuvir (SOF)/ledipasvir in 147 cases, ritonavir‐boosted ombitasvir/paritaprevir in 28 cases, elbasvir/grazoprevir in 19 cases, and SOF/ribavirin in 48 cases. The patients' histories included hepatocellular carcinoma (HCC) in 45 cases, liver transplant (LT) in 10 cases, and kidney transplant (KT) in 17 cases. Results: Sustained virological responses occurred in 335 cases (96%). DAA treatment was initiated a median of 16.3 months after HCC treatment. After DAA treatment, 15 cases (33%) had recurrence of HCC after a median of 11.6 months, and 3 cases (1%) developed de novo HCC. Six LT patients and one KT patient had HCC; however, no HCC was observed after DAA. The incidence of HCC was significantly higher in patients with multiple HCC treatments in the Cox hazard model (hazard ratio 1.664, 95% confidence interval 1.134–2.441, P < 0.01). Surgical resection or LT reduced the risk of HCC. Conclusions: DAA did not increase the rate of HCC, even in immunosuppressed patients. However, careful follow‐up for HCC recurrence is required in previously treated cases. Abstract : Direct‐acting antivirals did not increase the rate of hepatocellular carcinoma (HCC), even in immunosuppressed patients. However, careful follow‐up for HCC recurrence is required in previously treated cases.